Plasma immersion ion implantation of nitrogen into H13 steel under moderate temperatures - Ueda, M.; Leandro, C. [UNESP]; Reuther, H.; Lepienski, C. M. (Elsevier B.V., 2005)
Ion implantation of nitrogen into samples of tempered and quenched H13 steel was carried out by plasma immersion technique. A glow discharge plasma of nitrogen species was the ion source and the negative high voltage pulser provided 10-12 kV, 60 mu s duration and 1.0-2.0 kHz frequency, flat voltage pulses. The temperatures of the samples remained between 300 and 450 degrees C, sustained solely by the ion bombardment. In some of the discharges, we used a N-2 + H-2 gas mixture with 1:1 ratio. PIII treatments as long as 3, 6, 9 and up to 12 h were carried out to achieve as thickest treated layer as possible, and we were able to reach over 20 mu m treated layers, as a result of ion implantation and thermal (and possibly radiation enhanced) diffusion. The nitrogen depth profiles were obtained by GDOS (Glow Discharge Optical Spectroscopy) and the exact composition profiles by AES (Auger Electron Spectroscopy). The hardness of the treated surface was increased by more than 250%, reaching 18.8 GPa. No white layer was seen in this case. A hardness profile was obtained which corroborated a deep hardened layer, confirming the high efficacy of the moderate temperature PIII treatment of steels. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: nitrogen implantation; H13 steel; plasma immersion ion implantation